-2z+4z=3z+5+2

Simple and best practice solution for -2z+4z=3z+5+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z+4z=3z+5+2 equation:


Simplifying
-2z + 4z = 3z + 5 + 2

Combine like terms: -2z + 4z = 2z
2z = 3z + 5 + 2

Reorder the terms:
2z = 5 + 2 + 3z

Combine like terms: 5 + 2 = 7
2z = 7 + 3z

Solving
2z = 7 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
2z + -3z = 7 + 3z + -3z

Combine like terms: 2z + -3z = -1z
-1z = 7 + 3z + -3z

Combine like terms: 3z + -3z = 0
-1z = 7 + 0
-1z = 7

Divide each side by '-1'.
z = -7

Simplifying
z = -7

See similar equations:

| 4y+3=3(2-Y) | | 4z-9z=8z+2+6z | | 9-b=2 | | 0.80(x+200)=0.07x+20 | | 8x+x^2=200 | | 13q+15=5-13q | | 4x^3-54x^2+180x-100=0 | | X+0.25x=5 | | (1-i)(1+2i)(1-3i)=0 | | (1-j)(1+2j)(1-3j)=0 | | 4h-3(2-h)=2(h+7) | | 200=8x+x^2 | | 1.6=log(x/5) | | -5-2y=5 | | 4x-3(6+2x)=-14 | | v=u | | cos^2x-cos-2=0 | | 60=2h-7+7 | | 2x^2-4x+p=0findvaluesp | | x^3-12x^2+60x-48=0 | | -10.5z-63=2z-15 | | 2n+7=5n-8 | | (x*10)/100=110-x | | 2(4a+5)+134=80(a+9) | | 4a2-a/a | | y=99.828x | | log(x)=1.79 | | 2.0317x^2+65.56x=0 | | y=2.0317x^2+65.56x | | 5x-19=2x+12 | | 21/57 | | f(x)=x(2x-1)(x+4) |

Equations solver categories